Ozone sensing by In2O3 films modified with rh: Dimension effect [Articol] - Korotcenkov, Ghenadii; Nehasil, Vaclav (MDPI, 2021)
We considered the effect of coverage of the surface of In2O3 films with rhodium on the sensitivity of their electrophysical properties to ozone (1 ppm). The surface coverage with rhodium varied in the range of 0–0.1 ML. The In2O3 films deposited by spray pyrolysis had a thickness of 40–50 nm. The sensor response to ozone depends on the degree of rhodium coverage. This dependence has a pronounced maximum at a coverage of ~0.01 ML of Rh. An explanation is given for this effect. It is concluded that the observed changes are associated with the transition from the atomically dispersed state of rhodium to a 3D cluster state.
Copyright: © 2021 by the authors. Licensee MDPI, Basel, Switzerland. This article is an open access article distributed under the terms and conditions of the Creative Commons Attribution (CC BY) license (https:// creativecommons.org/licenses/by/ 4.0/)
Keywords: surface modification; atomic dispersion; clustering; conductometric response; adsorption; decomposition; modeling